1999
DOI: 10.1016/s0002-9270(98)00730-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous microwave coagulation therapy for solitary metastatic liver tumors from colorectal cancer: a pilot clinical study

Abstract: PMCT is a safe and effective treatment for metachronous small liver tumors that have metastasized from colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…Local ablative techniques that result in intrahepatic tumor destruction have emerged as alternative treatment options, although positive effects on patients' survival remain to be established. These techniques include microwave tumor coagulation (19), laser-induced thermotherapy (20), injection of ethyl alcohol (21), cryosurgical ablation or cryotherapy (CSA) (22), and radiofrequency ablation (RFA) (23).…”
Section: Monitoring Responses After Local Ablative Therapy Of Liver Mmentioning
confidence: 99%
“…Local ablative techniques that result in intrahepatic tumor destruction have emerged as alternative treatment options, although positive effects on patients' survival remain to be established. These techniques include microwave tumor coagulation (19), laser-induced thermotherapy (20), injection of ethyl alcohol (21), cryosurgical ablation or cryotherapy (CSA) (22), and radiofrequency ablation (RFA) (23).…”
Section: Monitoring Responses After Local Ablative Therapy Of Liver Mmentioning
confidence: 99%
“…Heat ablation of liver tumors can also be performed using microwave coagulation therapy or laser-induced thermotherapy [45][46][47]. Like RFA, these procedures can be performed during an open laparotomy, with laparoscopic or thoracoscopic guidance, or percutaneously.…”
Section: Greatest Diametermentioning
confidence: 99%
“…The effectiveness of these treatments is currently limited by the small zones of necrosis achieved with the rapid heating and desiccation of the tissue around the microwave or laser probes. Multiple insertions of the probes are required to treat tumors more than 1 cm in diameter with microwave coagulation therapy, or more than 2 cm in diameter with laser-induced thermal ablation [45][46][47]. Currently, the treatment complexity of placing multiple intratumoral probes and the cost for these microwave or laser systems (at least 10 times higher than RF generators and needle electrodes) are limiting the clinical utility of these alternative thermal ablation techniques.…”
Section: Greatest Diametermentioning
confidence: 99%
“…Percutaneous microwave coagulation therapy (PMCT) has been used for the local treatment of either hepatocellular carcinoma (HCC) or metastatic liver tumors (1)(2)(3)(4)(5). In previous studies, PMCT has demonstrated the feasibility of efficaciously treating small HCC measuring ≤2.0 cm in diameter with a 5-year survival rate of about 70% (3).…”
Section: Introductionmentioning
confidence: 99%